Whole system approaches to railway asset management - Litherland, Jack J.M. (2019)
As the world population continues to grow, the demand for rail transport increases. The requirements on railway networks already at capacity continues to expand. In 2017-2018 there were 1.7 billion passenger journeys made on the UK railway network, compared to just over 700 million in 1994. Yet the number of track kilometres in the UK has remained near constant over that same time period. These changes are making maintenance scheduling more challenging; increased usage is leading to faster degradation yet, with more trains per hour and services starting earlier and finishing later, the time available to perform maintenance is shrinking. In many areas, it is extremely difficult to build new railways as land is both limited and expensive, additionally there are a range of legal challenges. Therefore innovative approaches to railway asset management are needed to maximise the performance of the existing network.